2019
DOI: 10.1136/bcr-2018-226959
|View full text |Cite
|
Sign up to set email alerts
|

Complete resolution of erythrodermic psoriasis with first-line apremilast monotherapy

Abstract: Erythrodermic psoriasis (EP) is the most serious type of psoriasis with high morbidity and mortality. First-line recommended therapies for EP, cyclosporine and infliximab have significant adverse effects. Cyclosporine increases the risk of hypertension, leucopenia, infections and renal failure. Infliximab increases the risk of reactivation of tuberculosis, hepatitis B and histoplasmosis, and increases risk for hepatitis, autoantibody formation, congestive heart failure, demyelinating disorders, pancytopenia, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Interestingly, positivity of BerEP4 in MCC tumour cells was recently emphasized in the new WHO classification of skin tumours, 2 suggesting BerEP4 positivity as a potential pitfall in distinguishing BCC and MCC. However, in the literature, only 4 studies with a limited number of cases investigated EpCAM expression in MCC using various antibody clones [6][7][8][9] (Table 1).…”
Section: Berep4 Positivity In Merkel Cell Carcinoma: a Potential Diagmentioning
confidence: 99%
“…Interestingly, positivity of BerEP4 in MCC tumour cells was recently emphasized in the new WHO classification of skin tumours, 2 suggesting BerEP4 positivity as a potential pitfall in distinguishing BCC and MCC. However, in the literature, only 4 studies with a limited number of cases investigated EpCAM expression in MCC using various antibody clones [6][7][8][9] (Table 1).…”
Section: Berep4 Positivity In Merkel Cell Carcinoma: a Potential Diagmentioning
confidence: 99%
“…Apremilast, a phosphodiesterase 4 (PDE4) inhibitor, has been used for EP in four case reports. [112][113][114][115] Papadavid et al reported one case of a previous failure with MTX, cyclosporine and adalimumab, who achieved PASI 100 after apremilast 30 mg twice daily for 20 days. 112 Krishnamoorthy et al reported one case with the total resolution of the lesions after 10 weeks of treatment without relapse for 1 year.…”
Section: Others Apremilastmentioning
confidence: 99%
“…To the Editor: Apremilast is a phosphodiesterase 4 inhibitor that blocks proinflammatory effects and promotes anti-inflammatory effects of immunologic cells. 1 We were pleased to read about the success of Jeon et al 2 in using it for treating patients with multiple comorbidities for generalized pustular psoriasis. Similarly, we found meaningful results when patients with numerous comorbidities were treated with apremilast for erythrodermic psoriasis (EP), and we believe that many would find our cases worth reviewing.…”
mentioning
confidence: 99%
“…Historically, cyclosporine has been the first-line therapy, with methotrexate and acitretin as close seconds only because of their slower onset of action. 1 , 3 More recently, biologics such as infliximab and ustekinumab have been at the forefront of treatment for EP. 3 Although not currently recognized as a first-line agent, we found that the oral agent apremilast offers promise in the treatment of EP as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation